Kad Hari Raya - A Kadir, Adam; Adam, Maniseh; Adam, Tiwi Adlin; Adam, Wira Izran; Adam, Nur Mawarni (Nil, 1978)
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Adam A.Kadir, Maniseh Adam, Tiwi Adlin Adam, Wira Izran Adam dan Nur Mawarni Adam